Reduced RNA polymerase II transcription in intact and permeabilized Cockayne syndrome group B cells - Balajee, Adayabalam S. (The National Academy of Sciences of the USA, 1997)
Cockayne syndrome (CS) is characterized by increased photosensitivity, growth retardation, and neurological and skeletal abnormalities. The recovery of RNA synthesis is abnormally delayed in CS cells after exposure to UV radiation. Gene-specific repair studies have shown a defect in the transcription-coupled repair (TCR) of active genes in CS cells from genetic complementation groups A and B (CS-A and CS-B). We have analyzed transcription in vivo in intact and permeabilized CS-B cells. Uridine pulse labeling in intact CS-B fibroblasts and lymphoblasts shows a reduction of ≈50% compared with various normal cells and with cells from a patient with xeroderma pigmentosum (XP) group A. In permeabilized CS-B cells transcription in chromatin isolated under physiological conditions is reduced to about 50% of that in normal chromatin and there is a marked reduction in fluorescence intensity in transcription sites in interphase nuclei. Transcription in CS-B cells is sensitive to α-amanitin, suggesting that it is RNA polymerase II-dependent. The reduced transcription in CS-B cells is complemented in chromatin by the addition of normal cell extract, and in intact cells by transfection with the CSB gene. CS-B may be a primary transcription deficiency.